(untitled) (Baghdad Science Journal, 2023)
Breast cancer is the most repeatedly detected cancer category and the second reason cause of cancer-linked deaths among women worldwide. Tumor bio-indictor is a term utilized to describe possible indicators for carcinoma diagnosis, development and progression. The goal of this study is to evaluate part of some cytokines and biomarkers for both serum and saliva samples in breast cancer then estimate their potential value in the early diagnosis of breast cancer by doing more researches in saliva, and utilizing saliva instead of blood (serum and plasma) in sample collection from patients. Serum and salivary samples were taken from 72 patients with breast cancer and 45 healthy controls, in order to investigate the following cytokines such as: interleukin 12 (IL-12), interleukin 6 (IL-6), interleukin 4 (IL-4), 8-hydroxydeoxyguanosine (8-OHdG), tumor necrosis factor (TNF) and interferon-γ (IFN-γ) levels with other bio-pointers such as: malondialdehyde (MDA), catalase, and 8-nitroguanine (8-NG). The results displayed that the levels of blood and saliva samples of IL-12 (P<0.0001), IL-6 (P<0.0001), IL-4 (P<0.001), 8-OHdG (P<0.0001), 8-NG (P<0.001, and P<0.004), TNF (P<0.002, and P<0.001) and IFN-γ (P<0.0001) were significantly higher in breast cancer, whereas there were significant lowering (P<0.0001) in catalase activates in breast cancer in both samples as compared with healthy subjects. The exchanging of blood to salivary components evaluation in this investigation may be utilized as a diagnostic tool, and designates the potential part for MDA, Catalase, and cytokines as important biochemical in breast cancer. Accordingly, the salivary diagnosis embraces a non-invasive process and tumor progression in breast malignancy patients. Beside saliva may well signify as an active new gate as blood evaluation but easier and cheaper.